Whose Ears Are These? - Peg Hall (U.S.A Picture Window Book, 2003)
Examines a variety of animal ears, noting how they look different and function in different ways. Animals shown include an African elephant, a cottontail rabbit, a brown bat, a gorilla, a desert fox, a sea lion, and a barn owl.
Sr.Kg
Keywords: PY-UOI-Sharing the Planet -- PY-UOI-Sharing the Planet; Endangered Species; Endangered Species